2022
DOI: 10.1002/cjoc.202200186
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Bimodal Distributed Cyclic Olefin Copolymers with Improved Tensile Properties

Abstract: Ethylene/norbornene(NBE) copolymers are the most representative and widely-used cyclic olefin copolymers (COCs). Higher NBE content in COCs leads to higher transparency, glass transition temperature and mechanical strength, but also makes the COC more brittle and therefore hampers its end uses. In this study, to improve the brittleness of COCs while maintaining their high strength, heat-resistant and transparency, bimodal distributed COCs have been prepared via two selective catalysts reactive blending in one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…[1][2][3][4][5][6][7] Furthermore, COCs display lower moisture absorption, better radiation resistance and lower birefringence compared to the common optical plastics as polymethylmethacrylate (PMMA) and polycarbonate (PC). [8][9][10][11][12] Therefore, COCs could be employed as an ideal alternative of PMMA and PC in various fields. As a typical COCs, copolymer of ethylene with norbornene (NBE) shows decent thermal resistance and high transparency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] Furthermore, COCs display lower moisture absorption, better radiation resistance and lower birefringence compared to the common optical plastics as polymethylmethacrylate (PMMA) and polycarbonate (PC). [8][9][10][11][12] Therefore, COCs could be employed as an ideal alternative of PMMA and PC in various fields. As a typical COCs, copolymer of ethylene with norbornene (NBE) shows decent thermal resistance and high transparency.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclic olefin copolymers (COCs) always show high transparency, outstanding chemical resistance, and dimensional stability 1–7 . Furthermore, COCs display lower moisture absorption, better radiation resistance and lower birefringence compared to the common optical plastics as polymethylmethacrylate (PMMA) and polycarbonate (PC) 8–12 . Therefore, COCs could be employed as an ideal alternative of PMMA and PC in various fields.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, recent studies have shown that the elastic properties can also be installed through branching formation via chain walking homopolymerization of ethylene [28–32] . The incorporation of cyclic comonomers such as norbornene endows cyclic olefin copolymers ( COC ) with unique properties such as high heat stability, good chemical resistance, low density and high transparency [33–35] …”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31][32] The incorporation of cyclic comonomers such as norbornene endows cyclic olefin copolymers (COC) with unique properties such as high heat stability, good chemical resistance, low density and high transparency. [33][34][35] To efficiently prepare the abovementioned copolymers, the catalysts must possess high reactivity toward these comonomers, along with the capabilities of incorporating a large amount of comonomers. The design and development of highperformance copolymerization catalysts are crucial for the further evolution of these copolymer materials.…”
Section: Introductionmentioning
confidence: 99%
“…One shortcoming of the optical properties in these notable COC materials is the relatively low refractive indices of 1.52–1.54, however. How to enhance the refractive index of COC is a paramount but greatly challenging project, because even a small increase on the refractive index makes a great impact on optical materials in terms of diverse design; and much less attention has been paid to produce novel high refractive index COC, although numerous COCs have been disclosed and studied. , In principle, introducing an atom or a substituent with a high molar refraction into the polymer chain can increase the intrinsic refractive index of the material, and these atoms or groups including sulfur, aromatic groups, halogens (except fluorine) are significantly promising candidates . Particularly, the carbazole unit stands out from these high refractive index groups including diphenylmethane ( n = 1.578), fluorene ( n = 1.640), o -phenylphenol ( n = 1.610), diphenylamine ( n = 1.636), and carbazole ( n = 1.708) …”
mentioning
confidence: 99%